Biological Control of Streptomyces sp. PR69 Against Phytophthora capsici and Its Growth-Promoting Effects on Plants - Perla Karina López-Reyes; Susana De la Torre-Zavala; María Mercedes Cortés-González; Luis Jesús Galán-Wong; Hamlet Avilés-Arnaut (Horticulturae, 2024)
Actinomycetes are a group of bacteria that have been reported as potential controllers of several plant pathogens and plant growth-promoting agents. This study focused on the isolation of 60 actinobacterial strains from the Cuatro Cienegas Basin, Coahuila, Mexico, with an emphasis on evaluating their potential as biocontrol agents against plant pathogens. Among the strains tested, the isolate PR69 exhibited significant in vitro antagonistic activity against eight plant pathogens, with inhibition rates ranging from 44% to 73%, including Phytophthora capsici. The genome of PR69 was sequenced and assembled. It was identified as Streptomyces by phylogenetic analysis based on concatenated multiple sequence alignments of 81 core bacterial genes. Additionally, volatile compounds produced by PR69 enhanced the growth of Arabidopsis thaliana seedlings in vitro, increasing seedling weight, primary root length, and the number of secondary roots. Furthermore, the soil treated with Streptomyces sp. PR69 effectively controlled the infection caused by the pathogen P. capsici in bell pepper plants, reducing mortality by 47% compared to plants inoculated solely with the pathogen. PR69-treated plants also showed 30% increase in fresh weight compared to untreated controls. These findings suggest that Streptomyces sp. PR69 holds promise as a bioinoculant for promoting pepper plant growth and controlling P. capsici populations.